Program Wirausaha Muda Bank Mandiri sebagai Implementasi Corporate Social Responsibility Sesuai PP No. 47/2012 - Akhyar, Dani Miftahul (Universitas Tribhuwana Tunggadewi, 2024)
Changes in the business competition landscape have forced companies to realize the importance of managing and improving a positive reputation in the eyes of stakeholders, one of which is done by creating a corporate social responsibility (CSR) program. This research discusses the implementation of CSR which is carried out in improving the company's reputation through its implementation in the